2017
DOI: 10.1007/s00586-017-4975-0
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Rosai–Dorfman disease: case report and literature review

Abstract: RDD with spinal involvement is uncommon and it is challengeable in making a certain diagnosis. Histopathologic characteristics and immunohistochemical findings are considered as the key points for the diagnosis of this disease. The optimal treatment remains controversial, and more efforts should be focused on the investigation of etiology and adjuvant therapy for relapsing cases or subresected lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 60 publications
0
11
1
Order By: Relevance
“…The mean age of spinal RDD is 34.7 years (range 2.5–78 years) with a male predominance (M/F = 1.48) with 71.4% of cases of spinal RDD being isolated, 21.4% of cases have associated lymphadenopathy, and 19.7% of patients have intracranial lesions simultaneously. [ 28 ] Before our case (case-no.1), only one case of skull involvement reported by Allegranza et al . in 1991,[ 3 ] making it be an extremely rare occurrence.…”
Section: Discussionmentioning
confidence: 88%
“…The mean age of spinal RDD is 34.7 years (range 2.5–78 years) with a male predominance (M/F = 1.48) with 71.4% of cases of spinal RDD being isolated, 21.4% of cases have associated lymphadenopathy, and 19.7% of patients have intracranial lesions simultaneously. [ 28 ] Before our case (case-no.1), only one case of skull involvement reported by Allegranza et al . in 1991,[ 3 ] making it be an extremely rare occurrence.…”
Section: Discussionmentioning
confidence: 88%
“…Spinal involvement in RDD is uncommon, manifesting as extramedullary dural-based lesions in most cases (4). Most lesions present as homogeneous, iso to hypointense masses on T2W images with or without perilesional edema, a presentation that closely mimics meningiomas (31,32). Distinction from this more commonly occurring imaging abnormality usually requires histologic confirmation.…”
Section: Discussionmentioning
confidence: 99%
“…Distinction from this more commonly occurring imaging abnormality usually requires histologic confirmation. Rarely, the presence of bone hyperostosis may enable the differentiation (32).…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective analysis on clinical records dated from 1969 to 2016 revealed that only 60 cases of isolated spinal RDD were reported during this time period. [ 7 ] Of these 60 cases, a significant majority of them (58 cases) were extramedullary dura-based lesions with intramedullary lesions affecting only 2 patients. [ 7 ] Interestingly, Chhabria et al [ 8 ] has reported RDD presenting as Conus–Cauda syndrome in which the mass lesion extended from the cauda equina to the sacral level.…”
Section: Discussionmentioning
confidence: 99%
“…[ 7 ] Of these 60 cases, a significant majority of them (58 cases) were extramedullary dura-based lesions with intramedullary lesions affecting only 2 patients. [ 7 ] Interestingly, Chhabria et al [ 8 ] has reported RDD presenting as Conus–Cauda syndrome in which the mass lesion extended from the cauda equina to the sacral level. Our case report is of a 28-year-old patient who presented with an isolated epidural mass at the level of the thoracic vertebra, in the absence of intracranial lesions.…”
Section: Discussionmentioning
confidence: 99%